Identification of stably expressed QTL for heading date using reciprocal introgression line and recombinant inbred line populations in rice - Cheng, Lirui; Wang, Junmin; Ye, Guoyou; Luo, Chenggang; Xu, Jianlong; Li, Zhikang (Hindawi Limited, 2012)
Two sets of reciprocal introgression lines (ILs) and a population of recombinant inbred lines (RILs) derived from the cross betweenjaponicacultivar Xiushui09 andindicabreeding line IR2061-520-6-9 (abbreviated as IR2061) were used to identify QTL for heading date (HD). Phenotyping was conducted in Hainan Island for two winter seasons (2007 and 2009). Nine QTLs were detected in the ILs with Xiushui09 background (XS-ILs), and four of which were repeatedly mapped across 2 years. Five QTLs were identified in the ILs with IR2061 background (IR-ILs), and three of which were commonly detected in 2 years. All commonly detected QTL had the same direction of gene effect. Seven QTL for HD were identified in the RILs in 2009. Only three (25%) QTLs were commonly detected using all the three populations (XS-ILs, IR-ILs and RILs). The number of commonly identified QTLs among populations was related to degree of similarity of their genetic backgrounds, suggesting that the genetic background effect is important for detecting HD QTL.QHd7andQHd10bstably expressed in different populations and across years thus would be exploited in rice breeding programme. Moreover, lines with both ofQHd7andQHd10bresulted in at least 3 days earlier than lines with only one of them QTL, showing evident pyramiding effect.